Falling for fun : gravity in action - Lepora, Nathan (Pleasantville, NY : Gareth Stevens, 2008)
Explains the science of gravity using roller coasters as examples, discussing such topics as acceleration, weight, g-forces, free fall, center of gravity, and kinetic and potential energy.
Gravity -- Weight -- G-forces and free fall -- Center of gravity -- Energy -- Kinetic energy -- Potential energy -- Conservation energy.
Includes index.
5.4
5-8
Keywords: Force and energy -- Juvenile literature; Gravity -- Juvenile literature; Force and energy; Gravity; Force and energy; Gravity